2018
DOI: 10.1080/14763141.2018.1478989
|View full text |Cite
|
Sign up to set email alerts
|

Movements with greater trunk accelerations and their properties during badminton games

Abstract: This study aimed to elucidate the movements requiring greater trunk accelerations and its frequencies during badminton games, and compare the acceleration components among such movements. Trunk acceleration was measured using a triaxial accelerometer during badminton games. The moments that generated >4 G resultant acceleration were extracted, and movements consistent with the extracted moments were identified. We calculated the extracted movement ratio and frequency and compared the resultant, mediolateral, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Moreover, Lam, Ding & Qu (2017) argued that an isolated lunge test using a controlled setting was far from the reality of interest in a competition. The relationship between isolated lunge, repeated lunge ( Lam, Ding & Qu, 2017 ), or uncontrolled lunge during a badminton game ( Nagano et al, 2020 ) required further investigations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, Lam, Ding & Qu (2017) argued that an isolated lunge test using a controlled setting was far from the reality of interest in a competition. The relationship between isolated lunge, repeated lunge ( Lam, Ding & Qu, 2017 ), or uncontrolled lunge during a badminton game ( Nagano et al, 2020 ) required further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Lunge manoeuvres can be performed in five directions, including three forward directions (forehand, backhand, and in-front) and two backward directions (forehand and backhand). Almost all included articles examined lunge biomechanics in forward direction, while one did not specify the direction of lunge ( Nagano et al, 2020 ). Three included articles considered backward lunges, and six compared the movement mechanics among lunge directions.…”
Section: Review Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on the landing posture after performing lateral jumps at different angles have reported that the valgus angle at the knee joint varies with changes in the landing direction (Stephenson et al, 2017). Some studies have used motion analysis to assess the risk of lower limb injuries, and one particular study of badminton players placed inertial measurement unit sensors on players' trunk to assess the differences between various badminton actions and paces (Nagano et al, 2018). Another study used inertial measurement unit (IMU) and image analysis to examine the around-the-head stroke performed in the backcourt and determined that backhand strokes resulted in a higher risk of injury (Sasaki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%